PENGINTEGRASIAN NILAI KARAKTER DALAM PEMBELAJARAN BIOLOGI PADA SEKOLAH MENENGAH ATAS DI TAKENGON DAN LHOKSEUMAWE - Eva Nauli Taib; Masri Masri (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2020)
This study aims to determine character values and how to integrate character values in biology learning in Takengon and Lhokseumawe. The method used in this study is a qualitative descriptive. This research was conducted in Takengon and Lhokseumawe districts involving 7 biology teachers in purposive sampling techniques. The data collection techniques used were observation, then conducted interviews with teachers and analysis of teacher RPP documents to find additional information as supporting data. The results showed that the character values integrated into biology learning in schools were concerned about health, religion, independence, tolerance, friendliness / communicative, social care, responsibility, and caring character of the environment. But the percentage of each character is different, the highest percentage (100%) are religious, independence, responsibility values for both regions and the lowest percentage (25%) values are health care and friendly/communicative in Takengon City, while in Lhokseumawe city the value of caring for the health, caring social and environmental care which have the lowest percentage (33,3%). Integration of character values is carried out in various ways, including refraction of greeting and prayer at the beginning and end of learning, chaplaincy, integration also done through learning models and media is one of the ways to integrate character in biology learning.